2022
DOI: 10.3390/fermentation8070303
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics, Prebiotics, Synbiotics, and Fermented Foods as Potential Biotics in Nutrition Improving Health via Microbiome-Gut-Brain Axis

Abstract: Biological, social, and psychological practices greatly affect the dietary intake of people; as a result, health-related complexities occur. Functional food and supplements have become popular due to their nutraceutical benefits, which make different choices of fermented food and beverages available to people. This review describes the characteristics of probiotics, prebiotics, post- and paraprobiotics, and their role in nutrition and in the sustainability of health. Currently, several synbiotic supplements ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 83 publications
1
54
0
4
Order By: Relevance
“…In regard to our finding, white dragon fruit extract at concentration less than or equal to 10% may serve as good growth for probiotic and have the potential to be added to the diet. Dahiya and Nigam (2022) stated that incorporation of oligosaccharide prebiotic into a diet in modest quantities of about 5 to 20 g per day stimulate the growth of bifidobacteria and lactobacilli in the intestine of adult. Fermentation of goat's milk with the addition of 10% white dragon fruit extract for kefir beverage Kefir is fermented milk produced by the activity of bacteria and yeast contained in the kefir grain starter culture, and reported as having unique taste of sour, creamy, and alcoholic scent (Farnworth 2005).…”
Section: Prebiotic Activity Scorementioning
confidence: 99%
See 1 more Smart Citation
“…In regard to our finding, white dragon fruit extract at concentration less than or equal to 10% may serve as good growth for probiotic and have the potential to be added to the diet. Dahiya and Nigam (2022) stated that incorporation of oligosaccharide prebiotic into a diet in modest quantities of about 5 to 20 g per day stimulate the growth of bifidobacteria and lactobacilli in the intestine of adult. Fermentation of goat's milk with the addition of 10% white dragon fruit extract for kefir beverage Kefir is fermented milk produced by the activity of bacteria and yeast contained in the kefir grain starter culture, and reported as having unique taste of sour, creamy, and alcoholic scent (Farnworth 2005).…”
Section: Prebiotic Activity Scorementioning
confidence: 99%
“…In their metabolism, probiotics provide beneficial effect to the host by producing compounds that have protective functions such as antibacterial, structural functions such as immune system development, and metabolic functions such as SCFA production, vitamins and minerals. Probiotics are live microorganisms that can be found either as supplements or as components in foods, which when foods are consumed the microorganisms are still found alive in the colon in an amount of at least 10 6 CFU/g and provide the health to the host (Dahiya and Nigam 2022). Probiotics must be able to overcome all obstacles when passing through the digestive tract in order to reach the colon and function to nourish the host.…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of fermented food, beverages, or supplements as the sources of probiotics restores gut health and the regular use of probiotic products sustains the gut microbiota. The intake of foods prepared with probiotic microbial strains is recommended through the outcomes of several studies, as they have been reported to influence human health and are effective in the relief of several diseases [ 3 , 4 ]. Probiotic and synbiotic foods can be prepared using non-dairy substrates to meet the requirement of all groups of consumers, including vegans and the population allergic to or with low digestibility of dairy products.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Research has confirmed that the gut microbiota significantly contributes to our general well-being [ 3 ]. Alteration of the composition of the gut microbiota can affect intelligence, mood, neurodevelopment, behaviour, and psychology of its host through the gut–brain partnership [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation